A new approach to removing and recovering phosphorus from livestock wastewater using dolomite. (September 2020) - Yin, Zhichao; Chen, Qingfeng; Zhao, Changsheng; Fu, Ying; Li, Jinye; Feng, You; Li, Lei
Abstract: Recovering phosphorus from livestock wastewater could partly mitigate the global phosphorus resource crisis. Crystallization is a promising method for removing phosphorus from wastewater, but the costs of calcium- and magnesium-containing reagents are increasing. Cheap, available, efficient materials are required to replace conventional calcium and magnesium reagents. Here, we describe a new approach to removing and recovering phosphorus from livestock wastewater of a large pig farm, containing a high phosphorus concentration. The effects of the pH, stirring speed, stirring time, and extract dose (containing calcium and magnesium) on phosphorus removal from livestock wastewater were investigated. The product was characterized by X-ray diffractometry, Fourier-transform infrared spectroscopy, and scanning electron microscopy. Under optimized conditions (pH 9.0, stirring speed 200 r/m, stirring time 600 s, Ca 207.62 mg/L, Mg 122.86 mg/L), 92% of the phosphorus was removed from livestock wastewater. The product was mainly the hydroxyapatite (Ca5 (PO4 )3 OH) precursor amorphous calcium phosphate but also contained 1.65% (by mass) magnesium ammonium phosphate (MgNH4 PO4 ·6H2 O) crystals. The cost of dolomite to treat 1 m 3 of high-phosphorus wastewater was 0.20 yuan (45.9%, 25.9%, and 75.9% lower than for pure MgCl2, MgSO4, and CaCl2, respectively) in 2019. Using dolomite to provide calcium and magnesium effectively decreases the crystallization process cost and should encourage the use of crystallization to remove phosphorus from wastewater. Graphical abstract: Image 1 Highlights: Dolomite can provide calcium and magnesium sources as cheap ore. The phosphorus removal rate for livestock wastewater was 92% under the optimal conditions. The cost of dolomite to treat high-phosphorus wastewater was at least 25.9% lower than the other chemicals raw material. Recovered product was mainly the HAP precursor ACP and 1.67% MAP.